INFORMATIZATION OF EDUCATION AND APPLICATION OF ICT FOR IMPROVEMENT OF ITS QUALITY - Dobroshtan, O.O. (Journal of Information Technologies in Education (ITE), 2010)
The article is devoted to the analysis of problems of informatization of formation of Ukraine, in particular, to access of students and teachers to electronic facilities of studies, networks are the Internet. Information is given on the place of IKT in maintenance of formation of general educational establishments. It is shown, that the decision factor of achievement of primary purpose of reformation of education is his informatization.